PELATIHAN PEMBUATAN HANDRUB SEBAGAI UPAYA PREVENTIF COVID-19 DI LINGKUNGAN PESANTREN - Raisya Hasina; Siti Rahmatul Aini; Iman Surya Pratama; Ni Made Amelia Ratnata Dewi; Candra Eka Puspitasari; Muhammad Abdurrahman Fardiaz; Nurmayanggi Aulia Safitri (Universitas Mataram, 2023)
One of the things that causes the rapid spread of the virus is dirty hands. To overcome this, you can do it by keeping your hands clean by using a handrub. Handrub is a health product that is widely used by people during the COVID-19 pandemic. This activity aims to train students to make handrubs and produce a health product that is used for the wider community as a way to prevent COVID-19 infection in Islamic boarding schools. The training was carried out at the Sekarbela Nurul Islam Islamic boarding school through lecture, discussion and practice methods with the aim of increasing knowledge through counseling activities and making handrub formulations as an effort to prevent COVID-19 infection in the pesantren environment. Partners in this community service activity are 23 students of Pondok Nurul Islam Sekarbela. This training activity was carried out by Mataram University lecturers in 4 stages, namely: preparation, counseling on material about Covid-19, PHBS Demonstration (Clean and healthy living behavior) and Handrub making activities in practice. The preparatory stage is in the form of discussions with the board of the Islamic boarding school for community service at Pondok Nurul Islam Sekarbela regarding the schedule for carrying out activities. The implementation phase is carried out in three sessions. The first session was to present counseling material about Covid-19. The second session was demonstrating PHBS (Clean and Healthy Living Behavior) and hand washing dance. The third stage is the practice of making handrub directly in front of the students. This service activity received a good response. From the implementation of this counseling activity, it can increase knowledge related to Covid-19 prevention, PHBS and students have skills in making handrub.